2019
DOI: 10.1080/25765299.2019.1632141
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis, characterization and investigation of antibacterial activity of 3-(5-(substituted-phenyl)-4,5-dihydro-1H-pyrazol-3-yl)-2H-chromen-2-one derivatives

Abstract: Microwave assisted synthesis, characterization and investigation of antibacterial activity of 3-(5-(substitutedphenyl)-4,5-dihydro-1H-pyrazol-3-yl)-2H-chromen-2-one derivatives,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this study, three enzymes were used as targets to inspect the potential of thiourea derivatives against MRSA, Gram-negative E. coli, and weak Gram-positive MTB. The synthesised thiourea derivative compounds contain aromatic groups, thio groups (C=S), and amides (H2N-C=O), which are commonly found in the class of antibacterial drugs (Merkl et al, 2010;Lucio et al, 2018;Ajani et al, 2019;Carmen et al, 2020). The synthesis reaction employed a nucleophilic substitution reaction (Figure 1).…”
Section: Designmentioning
confidence: 99%
“…In this study, three enzymes were used as targets to inspect the potential of thiourea derivatives against MRSA, Gram-negative E. coli, and weak Gram-positive MTB. The synthesised thiourea derivative compounds contain aromatic groups, thio groups (C=S), and amides (H2N-C=O), which are commonly found in the class of antibacterial drugs (Merkl et al, 2010;Lucio et al, 2018;Ajani et al, 2019;Carmen et al, 2020). The synthesis reaction employed a nucleophilic substitution reaction (Figure 1).…”
Section: Designmentioning
confidence: 99%
“…The result showed that the most active antibacterial agent was 3‐(5‐(4‐[diethylamino] phenyl)‐4,5‐dihydro‐1 H ‐pyrazol‐3‐yl)‐2 H ‐chromen‐2‐one 38 j with MIC and MBC values of 3.92 ± 0.22 and 7.82 ± 0.43 mg/mL respectively, that may be attributed to presence of N(Et) 2 moiety (Scheme 9). [ 73 ]…”
Section: Synthesismentioning
confidence: 99%